A variety of metal–organic and supramolecular networks constructed from a new flexible multifunctional building block bearing picolinate and terephthalate functionalities: hydrothermal self-assembly, structural features, magnetic and luminescent properties. Issue 106 (15th October 2015) - Shao, Yong-Liang; Cui, Yan-Hui; Gu, Jin-Zhong; Kirillov, Alexander M.; Wu, Jiang; Wang, Ya-Wen
Abstract : A novel multifunctional building block was designed and applied for the synthesis of diverse coordination compounds. Abstract : A novel flexible multifunctional building block (H3 L) bearing picolinate and terephthalate functionalities was designed and applied for the hydrothermal self-assembly generation of a series of coordination compounds [Co(H2 L)2 (H2 O)2 ] (1 ), [M(HL)(H2 O)] n M = Cd (2 ) and Mn (3 ), [Mn1.5 (L)(phen)(H2 O)2 ]·H2 O n (4 ), [Zn3 (L)2 (H2 O)6 ] n (5 ), and [Zn3 (L)2 (py) (H2 O)4 ]·4H2 O n (6 ) wherein H3 L = 2-(4-carboxypyridin-3-yl)-terephthalic acid, phen = 1, 10-phenanthroline, py = pyridine. All the obtained products1–6 were fully characterized by IR spectroscopy, elemental, thermogravimetric, powder and single-crystal X-ray diffraction analyses. By adjusting the molar ratio of NaOH and H3 L ligand, the latter becomes partially deprotonated to form the H2 L − blocks in1 and HL 2− moieties in2 and3, or completely deprotonated to create the L 3− units in4–6 . The structures of the obtained compounds range from a discrete 0D monomer1 and 1D coordination polymers4 and5 to 2D coordination polymers2 and3, and an intricate 3D metal–organic framework6 ; their detailed topological classification was also performed. The structures of1–5 are further extended [0D → 3D (1 ), 1D → 3D (4, 5 ), and 2D → 3D (2, 3 )] into supramolecular networks by means of multiple hydrogen bonds. The results reveal that the nature of metal(ii ) ion, molar ratio between NaOH and H3 L ligand, and the presence (optional) of auxiliary ligand play a significant role in determining dimensionality, topology and other structural features of the obtained products. Magnetic susceptibility measurements indicate that compounds3 and4 have dominating antiferromagnetic couplings between metal centers. Furthermore, luminescent properties of2, 5, and6 were also investigated.